Long-Term Complications and Influence on Outcome in Patients Surviving Spontaneous Subarachnoid Hemorrhage - Gerner, Stefan; Reichl, Jonathan; Custal, Christina; Brandner, Sebastian; Eyüpoglu, Ilker Yasin; Lücking, Hannes; Hölter, Philip; Kallmünzer, Bernd; Huttner, Hagen (Cerebrovascular Diseases, 2020)
BACKGROUND: While the short-term clinical outcome of patients with subarachnoid hemorrhage (SAH) is well described, there are limited data on long-term complications and their impact on social reintegration. This study aimed to assess the frequency of complications post-SAH and to investigate whether these complications attribute to functional and self-reported outcomes as well as the ability to return to work in these patients. METHODS: This retrospective single-center study included patients with atraumatic SAH over a 5-year period at a tertiary care center. Patients received a clinical follow-up for 12 months. In addition to demographics, imaging data, and parameters of acute treatment, the rate and extent of long-term complications after SAH were recorded. The functional outcome was assessed using the modified Rankin Scale (mRS; favorable outcome defined as mRS = 0-2). Further outcomes comprised self-reported subjective health measured by the EQ-5D and return to work for SAH patients with appropriate age. Multivariable analyses including in-hospital parameters and long-term complications were conducted to identify parameters independently associated with outcomes in SAH survivors. RESULTS: This study cohort consisted of 505 SAH patients of whom 405 survived the follow-up period of 12 months (i.e., mortality rate of 19.8%). Outcome data were available in 359/405 (88.6%) patients surviving SAH. At 12 months, a favorable functional outcome was achieved in 287/359 (79.9%) and 145/251 (57.8%) SAH patients returned to work. The rates of post-acute complications were headache (32.3%), chronic hydrocephalus requiring permanent ventriculoperitoneal shunting (VP shunt 25.4%) and epileptic seizures (9.5%). Despite patient's and clinical characteristics, both presence of epilepsy and need for VP shunt were independently and negatively associated with a favorable functional outcome (epilepsy: adjusted odds ratio [aOR] (95% confidence interval [95% CI]): 0.125 [0.050-0.315]; VP shunt: 0.279 [0.132-0.588]; both p < 0.001) as well as with return to work (aOR [95% CI]: epilepsy 0.195 [0.065-0.584], p = 0.003; VP shunt 0.412 [0.188-0.903], p = 0.027). Multivariable analyses revealed presence of headache, VP shunt, or epilepsy to be significantly related to subjective health impairment (aOR [95% CI]: headache 0.248 [0.143-0.430]; epilepsy 0.223 [0.085-0.585]; VP shunt 0.434 [0.231-0.816]; all p < 0.01). CONCLUSIONS: Long-term complications occur frequently after SAH and are associated with an impairment of functional and social outcomes. Further studies are warranted to investigate if treatment strategies specifically targeting these complications, including preventive aspects, may improve the outcomes after SAH.
CRIS-Team Scopus Importer:2020-08-07
Keywords: Long-term complications; Post-stroke outcomes; Social participation; Subarachnoid hemorrhage

Parenchymatous hematoma in patients with atraumatic subarachnoid hemorrhage: Characteristics, treatment, and clinical outcomes - Gerner, Stefan; Hülsbrink, Robert; Reichl, Jonathan; Mrochen, Anne; Eyüpoglu, Ilker Yasin; Brandner, Sebastian; Dörfler, Arnd; Engelhorn, Tobias; Kuramatsu, Joji; Schwab, Stefan; Huttner, Hagen (International Journal of Stroke, 2020)
Background: Data regarding the influence of concomitant parenchymatous hematoma (PH) on long-term outcomes in patients with atraumatic subarachnoid hemorrhage (SAH) are scarce. Further, it is not established if these patients benefit from surgical intervention. Aim: The aim of this study was to determine the influence of concomitant PH in SAH patients on functional long-term outcome, and whether these patients may benefit from surgical hematoma evacuation. Methods: Over a 5-year period, all consecutive patients with SAH treated at the Departments of Neurology, Neuroradiology, and Neurosurgery, at the University Hospital Erlangen (Germany) were recorded. In addition to the clinical and imaging characteristics of SAH, we documented the presence, location, and volume of PH as well as treatment parameters. Outcome assessment at 12 months included functional outcome (modified Rankin scale (mRS), favorable = 0–2), health-related quality of life, and long-term complications. For outcome analysis, a propensity score matching (ratio 1:1, caliper 0.1) was performed to compare SAH patients with and without PH. Sub-analyses were performed regarding PH treatment (surgical evacuation vs. conservative). Results: A total of 494 patients with atraumatic SAH were available. Eighty-five (17.2%) had PH on initial imaging. SAH patients with PH had a worse clinical condition on admission and had a greater extent of subarachnoid/intraventricular hemorrhage. Median PH volume was 11.0 ml (5.4–31.8) with largest volumes observed in patients with ruptured middle cerebral artery (MCA)-aneurysm (31.7 ml (16.3–43.2)). After propensity-score matching (PSM), patients with PH had worse functional outcomes at 12 months (modified Rankin scale (mRS) 0–2: PH 31.8% vs. ØPH57.7% p < 0.001), and a lower rate of self-reported health compared to patients without PH (EQ-5D VAS: PH 50(30–70) vs. ØPH 80(65–95); p < 0.001). In PH patients, surgical evacuation was associated with a higher rate of favorable outcome at 12 months compared to those treated conservatively (surgery 14/28 (50.0%) vs. conservative 14/57 (24.6%); adjusted odds-ratio (OR; 95%CI): 1.34 (1.08–1.66); p = 0.001), irrespective of aneurysm location. Subgroup-analysis revealed positive associations of surgical hematoma evacuation with outcome in subgroups with larger PH volumes (>10 ml; OR (95%CI): 1.39 (1.09–1.79)), frontal PH location (OR 1.59 (1.14–2.23)), and early surgery (within 600 min after onset; OR 1.42 (1.03–1.94)). Conclusions: Concomitant PH occurs frequently in patients with SAH and is associated with functional impairment after 1 year. Surgical evacuation of PH may improve outcomes in these patients, irrespective of aneurysm-location.
CRIS-Team Scopus Importer:2020-11-27
Keywords: Cerebral hemorrhage; complications; intracerebral hemorrahage; subarachnoid hemorrhage; surgery; treatment